Serious Games for the Development of Learning - El Azizi, Loubna; Arbai, Aziz (Transactions on Engineering and Computing Sciences, 2017)
With the advent of interactive media, learning by playing is taking a variety of forms. Serious game, this term may seem contradictory, in reality it reflexes a very current reality, it rests on the video culture playful learners. This type of games is appropriate for investing in classrooms, the idea is to make learning more interactive and motivating. They have been developed to enable learners to build their own knowledge, skills and know-how to develop high-level skills to deal with complex situations. In this paper, we present the concept of serious game, and our educational software who contain the attractive exercises and a serious game for mathematics.We design this softwarein Arabic to make mental calculation appreciate to novicestudents. And we believe that this type of software can be used to increasestudents’motivation to learn, and their interest in mental calculation.